Biophysical and Subject-Based Assessment of the Effects of Topical Moisturizer Usage on Xerotic Skin—Part I: EpsilonTM 2D Skin Hydration - Hans Stettler; Jonathan Crowther; Alison Boxshall; Stephan Bielfeldt; Bailu Lu; Raffaella de Salvo; Sonja Trapp; Peter Blenkiron (Cosmetics, 2021)
As new biophysical methods become available to the skin researcher, it is important to understand the type of information that they are capable of measuring, and how it relates to consumer perception of topical moisturizing products. This work was aimed at understanding how two-dimensional (2D) skin hydration mapping can be used to describe skin properties beyond the traditional ‘single number’ approach to skin hydration. Two-dimensional skin hydration measurement data were collected at baseline and after 1 week of in vivo usage of a topical moisturizing product. In addition, subject feedback regarding their skin condition obtained during the study was collected and assessed. Dividing the 2D hydration measurement device images into zones of different electrical permittivity scores enabled analysis of different aspects of the skin compared with traditional electrical skin hydration measurements. Improvement in skin flexibility as a result of use of the topical test product was demonstrated. Complete description of the skin’s hydration state through the creation of hydration histograms to describe its electrical characteristics was performed. Subject feedback data showed improvements in aspects of skin assessed using 2D hydration measurement.